Hubungan antara Pekerjaan dengan Prevalensi Dugaan Mati Mendadak di RSUD Dr. Moewardi pada Januari 2006âDesember 2011 - Kusumawaty, Aldila Desy (Nexus Kedokteran Komunitas, 2012)
Aldila Desy Kusumawaty, G0009010, 2012, The Relation of Work with Prevalence of Suspected Sudden Death in Hospital Dr. Moewardi in January 2006âDecember 2011. Mini Thesis. Medical Faculty of Sebelas Maret University, Surakarta. Background: The work environment impact on personâs health behavior. The existence of an excessive work load has a negative effect on worker health. Stress can cause cardiac arrhythmias and sudden death in susceptible people, perhaps through the center that is driven by the autonomic nervous system response. The purpose of this study was to determine the incidence of sudden death associated with the work load. Methods: This is a type of case-control study. Sample of this study was the victim of sudden death and people who live near or around the house of that sudden deathâs victims with total sample 88 people. The data was analyzed with Chi Square Test and multiple logistic regression analysis. Results: Found a statistically significant association between the incidence of sudden death with the work. People with heavy work will have sudden death risk about 3,46 times compared to those with light work (p= 0.046; OR= 3.46). Conclusions: Based on this study, people with heavy work will have a risk for sudden death 3,46 times greater than people with light work. Keywords: work, work load, sudden death.